Advanced Mechatronics Solutions - Jabłoński, Ryszard; Brezina, Tomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
Focusing on the most rapidly changing areas of mechatronics, this book discusses signals and system control, mechatronic products, metrology and nanometrology, automatic control & robotics, biomedical engineering, photonics, design manufacturing and testing of MEMS. It is reflected in the list of contributors, including an international group of 302 leading researchers representing 12 countries. The book is intended for use in academic, government and industry R&D departments, as an indispensable reference tool for the years to come. Thid volume can serve a global community as the definitive reference source in Mechatronics. The book comprises carefully selected 93 contributions presented at the 11th International Conference Mechatronics 2015, organized by Faculty of Mechatronics, Warsaw University of Technology, on September 21-23, in Warsaw, Poland. .
Automatic Control -- Biomedical Engineering -- Mechatronics Products: Design, Manufacturing and Testing -- Metrology and Nanometrology -- Nanotechnology, MEMS, New Materials -- Photonics, Vision Systems and Image Processing -- Robotics.
Keywords: Mechatronics; Control engineering; Robotics; Automation; Computational intelligence; Artificial intelligence; Mechatronics; Control, Robotics, Automation; Computational Intelligence; Artificial Intelligence